A compliant tuned liquid damper for controlling seismic vibration of short period structures. (1st October 2019) - Pandey, Dhirendra K.; Sharma, Mohit K.; Mishra, Sudib K.
Highlights: A compliant TLD is proposed to facilitate tuning and vibration control of short period structures. TLD parameters are optimized and improved performance over conventional TLD is established. The effectiveness of the response control is demonstrated by numerical simulation. Findings from simulation are substantiated experimentally by shake table testing. Effectiveness of the proposed TLD is demonstrated in a real building. Abstract: Tuning of sloshing frequency of liquid to short period structures possess challenges in Tuned Liquid Dampers (TLD). However, seismic vulnerability of short period structures cannot be overemphasized. In such instances, frequency tuning is facilitated by inserting a spring between the structure and the TLD. An implementation of this is presented herein by mounting the TLD on an array of compliant elastomeric pads, referred herein as compliant TLD. The effectiveness of compliant TLD is demonstrated through simulation that involve numerical solution of the derived equation of motion. The nonlinear sloshing, wave breaking and resulting dissipation are described by Sun's model. The infeasibility of tuning of conventional TLD to short period structures and consequent inefficiency are shown to be largely eliminated by the proposed implementation. Significant reductions in the peak and root mean square (r.m.s) floor accelerations and storey displacements are observed while (the structures are) subjected to a suite of ground motions pertaining to varying hazard level. The parameters for the proposed system are chosen based on the parametric variations of the controlled responses. The performances of the compliant TLD are also verified with experimental investigations using shake table test on scaled model of a building-TLD system. The experimental results corroborate with the trends observed from simulation. The tuning invoked by the compliant mechanism is observed to largely retain the sloshing and dissipation through wave breaking. Further, the design of the compliant TLD is presented and enumerated with an example of realistic building frame.